Geographies of Urban Female Labor and Nationhood in Spanish Culture, 1880–1975 - Soria, Mar (UNP - Nebraska, 2020)
Cover – Title Page – Copyright Page – Contents – Acknowledgments – Introduction – 1. The Castiza Working Woman – 2. Homebound Workers – 3. Commodifying the Nation – 4. Working for Change during the Second Republic – 5. Back Home? – 6. Spanish Women Are Different – Epilogue – Notes – References – Index.
Description based on publisher supplied metadata and other sources
Keywords: Women employees in literature; Women employees in motion pictures; Working class women in literature; Working class women in motion pictures; Motion pictures; Spanish literature; Motion pictures; Spain; History; Spanish literature; 19th century; History and criticism; Spanish literature; 20th century; History and criticism; Electronic books